MORPHOREGRESSION AND CONDITION OF FRIGATE TUNA (Auxis thazard LACEPÈDE, 1800) IN SOUTH COAST OF BALI STRAIT WATERS - Parawangsa, I Nyoman Yoga; Suryani, Sang Ayu Made Putri; Tampubolon, Prawira Atmaja; Wijayanti, Ni Putu Ayu; Lestari, Ni Made Dwi (Politeknik Kelautan dan Perikanan Sorong, 2025)
Bali Strait water has contributed to the production of pelagic capture fisheries in FMA-573. The potential for fisheries in the Bali Strait is very diverse, especially small pelagic fish such as frigate tuna, bullet tuna, bali sardinella, scad fish and mackerel. Frigate tuna (Auxis thazard) is a pelagic fish from the Scombridae family. This fish can be found in tropical and subtropical waters. Information regarding frigate tuna on the southern coast of the Bali Strait has yet to be found to date. This research aims to reveal morphoregression, which includes the length-length relationship and growth patterns, as well as the condition of frigate tuna in the southern coastal waters of the Bali Strait for ecosystem-based fisheries management. Sampling of frigate tuna was carried out from February to July 2024. Fish samples were taken from traditional fishermen who used gill nets as fishing gear in the southern coastal waters of the Bali Strait. Each fish sample was measured for total length, fork length, and standard length and weighed to analyze the length-length relationship, growth patterns, and condition factors. The number of frigate tuna caught during the research was 356. The total length of the samples caught ranged from 274 – 416 mm, weighing 270.3 – 972.4 grams. Each character of the length of the frigate tuna has a close relationship. The fork length character is the most precise in estimating fish weight, so the fork length character is used to analyze the length-weight relationship. The growth pattern of frigate tuna is positive allometric with good conditions. The results of this research can be used as a basis for ecosystem-based management of tuna fisheries.